2015
DOI: 10.4238/2015.june.18.14
|View full text |Cite
|
Sign up to set email alerts
|

Association between FTO polymorphism in exon 3 with carcass and meat quality traits in crossbred ducks

Abstract: ABSTRACT. The fat mass and obesity-associated gene (FTO) is an excellent candidate gene that affects energy metabolism. Single nucleotide polymorphisms (SNPs) in FTO are associated with carcass and meat quality traits in pigs, cattle, and rabbits. The aim of this study was to investigate the association between novel SNPs in the FTO coding region and carcass and meat quality traits in 95 crossbred ducks, using DNA sequencing. We found two transitions G/A (SNP 387 and 473) within exon 3. SNP 387 was a synonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…We found that neither slaughter age nor slaughter weight affected the carcass and meat quality traits in the studied population. This result was in agreement which reported by Gan et al (2015) that have measured meat quality in chinese duck crossbreed. Gan et al (2015) revealed pH, L*, a* and b* were 5,4; 35,29; 18,11 and 4,23 respectively.…”
Section: Phenotype Of Carcass and Meat Qualitysupporting
confidence: 94%
See 1 more Smart Citation
“…We found that neither slaughter age nor slaughter weight affected the carcass and meat quality traits in the studied population. This result was in agreement which reported by Gan et al (2015) that have measured meat quality in chinese duck crossbreed. Gan et al (2015) revealed pH, L*, a* and b* were 5,4; 35,29; 18,11 and 4,23 respectively.…”
Section: Phenotype Of Carcass and Meat Qualitysupporting
confidence: 94%
“…Mean live weight (LW) of the ducks was 1472.73 g. The average Carcass weight (CW), breast weight (BW), wing weight (WW) and leg weight (LMW) were 938.28 ± 116.07, 238.72 ± 51.51, 132.42 ± 12.97and 216.37 ± 28.29, respectively(Table 1). This result is lower that most previous duck carcass measurment in the literature Gan et al (2015). obtained CW and LW in Cherry Valley duck and Liancheng white were 1775.39 g and 1620.90 g.…”
contrasting
confidence: 68%
“…First, the number of specific genotypes (AG of SNP2 and CC of SNP3) was too small probable due to genetic drift [24]. Second, the economically favorable traits (such as low average wool fiber diameter) have been artificially selected and SNPs 2 and 3 as the beneficial SNPs or in linkage equilibrium with the beneficial SNPs might have been accumulated [25]. Last, the individual with different genotype may have different environmental adaptability and the individual with low environmental adaptability may be eliminated by natural selection [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with other domestic animals, study about the genetic basis of growth traits in ducks is lacking. Previous studies suggested that the fat mass and obesity-associated gene ( FTO ) [11] and mutations in intron 2 of the growth hormone gene ( GH ) [12] influenced duck carcass and meat quality traits, while Zhang et al [13] also showed that the perilin gene ( PLIN ) affected duck carcass and fat traits.…”
Section: Introductionmentioning
confidence: 99%